2017
DOI: 10.1177/2167702617696359
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Modification (ABM): Review of Effects of Multisession ABM Training on Anxiety and Threat-Related Attention in High-Anxious Individuals

Abstract: Attention bias modification (ABM) aims to reduce anxiety by reducing attention bias (AB) to threat; however, effects on anxiety and AB are variable. This review examines 34 studies assessing effects of multisession-ABM on both anxiety and AB in high-anxious individuals. Methods include ABM-threat-avoidance (promoting attention-orienting away from threat), ABM-positive-search (promoting explicit, goal-directed attention-search for positive/nonthreat targets among negative/threat distractors), and comparison con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
107
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(112 citation statements)
references
References 97 publications
(397 reference statements)
4
107
1
Order By: Relevance
“…Because we used an experimental study design, we could not examine the developmental change of cognitive biases for children. It should be mentioned that in line with previous studies (for an overview, see Mogg et al 2017), children in our study did not have a significant attention bias towards threat. In contrast to adults, the relative role of attention bias for children with anxiety seems to be minor (Abend et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Because we used an experimental study design, we could not examine the developmental change of cognitive biases for children. It should be mentioned that in line with previous studies (for an overview, see Mogg et al 2017), children in our study did not have a significant attention bias towards threat. In contrast to adults, the relative role of attention bias for children with anxiety seems to be minor (Abend et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…given the surge of interest in Attentional Bias Modification (ABM) research, in which changes in AB are experimentally induced to influence responsiveness to stress, our finding is still relevant and timely. Many ABM studies rely on a modified version of the VPT to induce changes in AB or have used the VPT to assess these changes in AB (for reviews, see Mogg et al, 2017;Van Bockstaele et al, 2014). Similar to the AB literature, the overall pattern of results in ABM studies is marked by inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…Results of individual studies using the VPT often diverge and the pattern of correlations between individual AB scores and measures of anxiety is highly inconsistent (Van Bockstaele et al, 2014), and even clinical samples often have no significant AB (e.g. Mogg, Waters, & Bradley, 2017). A likely cause of these inconsistencies is the VPT's poor reliability.…”
mentioning
confidence: 99%
“…For example, there is some evidence that more complex and engaging attentional distraction tasks can effectively reduce patients’ itch and scratching, whereas a simple distraction task seems ineffective . Also, a proof‐of‐principle attention bias modification training, as commonly used in different research areas with incongruent results, has not been shown to effectively retrain healthy individuals’ attention . Such attention training has not been studied in clinical itch samples.…”
Section: Discussionmentioning
confidence: 99%